UJI DAYA HAMBAT EKSTRAK RUMPUT LAUT Gracilaria verrucosa TERHADAP BAKTERI Vibrio harveyi - Mad Rudi; Dian Eka Ramadhani (Universitas Pendidikan Indonesia (UPI), 2022)
The objectives of this study were to investigate the antibacterial activity of G. verrucosa seaweed extract in inhibitory test on the growth pathogen bacteria V. harveyi at different doses. Paramater test included phytochemical test through the method of color visualization and inhibitory test using method agar diffusion with paper disk. Treatment of doses consisted of positive using Chloramphenicol antibiotic 10 mg/L, doses seaweed extract included A (500 mg/L), B (1000 mg/L), and C (1500 mg/L). The result of inhibitory test showed that all of dose extract G. verrucosa (treatment A, B, and C) was able to inhibit the growth of V. harveyi. The result of inhibitory test that treatment C obtained the highest inhibitory test. In conclusion, that seaweed extract of G. verrucosa has an antibacterial activity